CTRP1 Protein Enhances Fatty Acid Oxidation via AMP-activated Protein Kinase (AMPK) Activation and Acetyl-CoA Carboxylase (ACC) Inhibition - Peterson, Jonathan M. (American Society for Biochemistry and Molecular Biology, 2012)
We previously described the adipokine CTRP1, which has up-regulated expression following exposure to the anti-diabetic drug rosiglitazone and increased circulating levels in adiponectin-null mice (Wong, G. W., Krawczyk, S. A., Kitidis-Mitrokostas, C., Revett, T., Gimeno, R., and Lodish, H. F. (2008) Biochem. J. 416, 161–177). Although recombinant CTRP1 lowers blood glucose in mice, its physiological function, mechanisms of action, and roles in metabolic stress remain unknown. Here, we show that circulating levels of CTRP1 are strikingly reduced in diet-induced obese mice. Overexpressing CTRP1 in transgenic mice improved insulin sensitivity and decreased high-fat diet-induced weight gain. Reduced adiposity resulted from enhanced fatty acid oxidation and energy expenditure, effects mediated by AMP-activated protein kinase (AMPK). In skeletal muscle of transgenic mice, AMPKα and its downstream target, acetyl-CoA carboxylase (ACC), were hyperphosphorylated, indicative of AMPK activation and ACC inhibition. Inactivation of ACC promotes mitochondrial fat oxidation. Consistent with the direct effect of CTRP1 on AMPK signaling, recombinant CTRP1 administration acutely stimulated muscle AMPKα and ACC phosphorylation in vivo. In isolated soleus muscle, recombinant CTRP1 activated AMPK signaling to increase fatty acid oxidation ex vivo, an effect abrogated by an AMPK inhibitor. These results provide the first in vivo evidence that CTRP1 is a novel regulator of fatty acid metabolism.